Measuring agility in tennis, badminton, and squash: a systematic review - Jansen, M. G. T.; Huijgen, B. C. H.; Faber, I. R.; Elferink-Gemser, M. T. (Strength and Conditioning Journal, 2021)
A systematic review in PubMed, Web of Science, SPORTDiscus, PsycINFO, and Google Scholar was conducted to provide a state-of-the-science overview of agility tests in the racquet sports tennis, badminton, and squash while evaluating their measurement properties. Twenty articles were included covering 28 agility tests. Results showed 10 sport-specific agility tests of which 5 were assessed on reliability and 6 on validity. Both the Badcamp and the badminton-specific speed ("agility") test were identified as suitable agility tests available for badminton. For tennis and squash, there were no sport-specific agility tests identified in the literature showing both reliable and valid results. Future research should focus on developing sport-specific agility tests for tennis and squash, including assessment of the reliability and validity of the tests.